Role of the NLRP3 Inflammasome: Insights Into Cancer Hallmarks - Lin, Ting-Yi; Tsai, Meng-Chun; Tu, Wei; Yeh, Hsin-Chih; Wang, Shu-Chi; Huang, Shu-Pin; Li, Chia-Yang (Frontiers in Immunology, 2021)
In response to a variety of stresses, mammalian cells activate the inflammasome for targeted caspase-dependent pyroptosis. The research community has recently begun to deduce that the activation of inflammasome is instigated by several known oncogenic stresses and metabolic perturbations; nevertheless, the role of inflammasomes in the context of cancer biology is less understood. In manipulating the expression of inflammasome, researchers have found that NLRP3 serves as a deterministic player in conducting tumor fate decisions. Understanding the mechanistic underpinning of pro-tumorigenic and anti-tumorigenic pathways might elucidate novel therapeutic onco-targets, thereby providing new opportunities to manipulate inflammasome in augmenting the anti-tumorigenic activity to prevent tumor expansion and achieve metastatic control. Accordingly, this review aims to decode the complexity of NLRP3, whereby summarizing and clustering findings into cancer hallmarks and tissue contexts may expedite consensus and underscore the potential of the inflammasome in drug translation.